Analysis of vulnerability, its drivers, and strategies applied towards reducing the pastoral and agro-pastoral livelihood vulnerability to climatic shocks - Daniel Assefa Tofu; Tegegn Dilbato; Chalchisa Fana; Niguse Bekele Dirbaba; Gutu Tesso (Scientific Reports)
Abstract In recent decades, the global climate has changed mainly due to human-induced causes and realizing their manifestations in the forms of extreme events such as droughts, floods, heat stress, and variability in rainfall. Arid and semi-arid ecosystems are sensitive to changes in climate variability, including the Borana zone. This study was therefore initiated to assess how vulnerable pastoral and agro-pastoral livelihoods are to climate change, as well as to estimate the effects, and pinpoint potential response measures that could be implemented in the study area. Data were gathered by surveys, focused group and expert group discussions. The quantitative data were analyzed through descriptive and inferential statistics, while the qualitative data was analyzed using thematically organized content analysis. The findings indicate that there is high degree of climatic risk to the livelihoods of both pastoralists and agro-pastoralists (− 0.37). The ability of pastoralists to adapt in comparison to agro-pastoralists is largely determined by numbers of factors, including inadequate livelihood strategies, poor access to social safety networks and services, knowledge and communication gaps, and availability of water resources. The area was extremely susceptible to the effects of climate change, which led to disaster. The primary outcome, which also affects other sources of income, is the loss of livestock (97%) which is followed by food shortages (91%), decreased income (84%), feed scarcity (83%), water scarcity (80%), and crop failure (79%). Managing livestock, taking advantage of social capital, storing hay and crop residue, and destocking animals during the period of severe drought were the main strategies used to reduce the vulnerability and enhance the adaptive capacity. Furthermore, despite the government’s numerous efforts to lesson enduring vulnerabilities and their effects, progress has not been encouraging because of lack of proactive action when faced with emergences. Hence, in order to decrease vulnerability and increase adaptive capacity, policymakers and development practitioners should collaborate proactively and develop area-specific adaptation strategies. These might include income diversification, increased access to water and pasture; installation of easily accessible market channels; and establishment of early warning systems that assist community preparation and resilience.